Peningkatan Kapasitas Kader Melalui Pelatihan Pengukuran Antropometri di Posyandu Melati Kota Bogor - Putra, Muh. Guntur Sunarjono; Anggiruling, Dwikani Oklita; Amrinanto, Ahmad Hisbullah; Muthmainah, Nadzira Inayah (Ikatan Sarjana Gizi Indonesia, 2024)
Nutritional problems are a problem that is still a challenge in Indonesia and in various regions, especially Bogor City, which still has a high prevalence of nutritional problems, such as stunting of 18.7% and underweight of 13%. With the anthropometric measurement training for cadres, it is hoped to increase the accuracy of data on nutritional status. The series of activities include the delivery of material related to anthropometric measurement standards in the form of power points and practicing anthropometric measurements using various measuring devices. This training activity can increase the knowledge score of cadres regarding procedures for validating anthropometric measurements, how to measure, the importance of proper measurements, and the interpretation of each measurement marked by a post-test score of 28.6 points greater than the pre-test score. Anthropometric measurement training positively influences cadres' knowledge of the importance of proper anthropometric measurements.